2019
DOI: 10.3390/jcm8081133
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Post-Operative Analgesic Efficacy of Low-Concentration High-Volume and High-Concentration Low-Volume Combinations of Ropivacaine for Transverse Abdominis Plane Block in Pediatric Open Inguinal Hernia Repair

Abstract: Transverse abdominis plane (TAP) block can provide post-operative analgesia in children undergoing open inguinal hernia repair. However, the optimal anesthetic dose, and concentration for TAP block in the pediatric population, is not well defined. This study compared the post-operative analgesic effect of TAP block between low-concentration, with high-volume (LCHV) and high-concentration, with low-volume (HCLV) combinations of local anesthetic. Forty-four patients who underwent open inguinal hernia repair were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Niiyama et al [ 11 ] compared the continuous infiltration of 0.2% ropivacaine with a single infiltration of 0.75% ropivacaine in patients undergoing microtia reconstruction surgery. Lee et al [ 12 ] also compared low-concentration ropivacaine and high-concentration ropivacaine in transverse abdominis plain blocks in pediatric open inguinal hernia repair. Han et al [ 13 ] and Tian et al [ 14 ] reported the analgesic effects of different ropivacaine concentrations in patients undergoing hip replacement and laparotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Niiyama et al [ 11 ] compared the continuous infiltration of 0.2% ropivacaine with a single infiltration of 0.75% ropivacaine in patients undergoing microtia reconstruction surgery. Lee et al [ 12 ] also compared low-concentration ropivacaine and high-concentration ropivacaine in transverse abdominis plain blocks in pediatric open inguinal hernia repair. Han et al [ 13 ] and Tian et al [ 14 ] reported the analgesic effects of different ropivacaine concentrations in patients undergoing hip replacement and laparotomy.…”
Section: Discussionmentioning
confidence: 99%